MENAVIGASI PERSIMPANGAN MODERNITAS DAN TRADISI : KEGIGIHAN RAMBU SOLO' DI MASYARAKAT TORAJA KONTEMPORER - Aulia H.R, Qalbi; Mukramin, Sam'un; Ismail, Lukman (SOSIORELIGIUS, 2024)
Rambu solo’ is a traditional ceremony of the Toraja community that requires the family of the deceased to make a party as a sign of last respect for the deceased who has passed away. The custom, which has been passed down from generation to generation by the Toraja Community, requires the family to perform the last ceremony for the deceased. The purpose of this study is to understand the role and sustainability of Rambu Solo’ in the midst of the dynamics of modernity in contemporary Toraja society and to intintrate the strategies used by the community to maintain and preserve the tradition of Rambu Solo. This research is qualitative with a library research approach, namely by collecting data by understanding and studying theories from various literature related to this research. This research is expected to provide a deeper understanding of how traditions such as Rambu Solo’ remain relevant and preserved in societies facing the pressures of modernity. The results of this study show that the belief system adopted by the Toraja Tribe in the time of their ancestors is the belief in Aluk Todolo where the Toraja Tribe believes in the creator of heaven and earth, known as Puang Matua. This research also shows that the Rambu Solo’ traditional ceremony contains values that describe the indigenous people of the Toraja tribe such as: Tolong-mentohelp, Gotong-royong, and Family.